Action and familiarity effects on self and other expert musicians’ Laban effort-shape analyses of expressive bodily behaviors in instrumental music performance: a case study approach - Broughton, Mary C.; Davidson, Jane W. (Frontiers in Psychology, 2014)
Self-reflective performance review and expert evaluation are features of Western music performance practice. While music is usually the focus, visual information provided by performing musicians’ expressive bodily behaviors communicates expressiveness to musically trained and untrained observers. Yet, within a seemingly homogenous group such as one of musically trained individuals, diversity of experience exists. Individual differences potentially affect perception of the subtleties of expressive performance, and performers’ effective communication of their expressive intentions. This study aimed to compare self- and other expert musicians’ perception of expressive bodily behaviors observed in marimba performance. We hypothesised that analyses of expressive expressive bodily behaviors differ between expert musicians according to their specialist motor expertise and familiarity with the music. Two professional percussionists and experienced marimba players, and one professional classical singer took part in the study. Participants independently conducted Laban effort-shape analysis – proposing that intentions manifest in bodily activity are understood through shared embodied processes – of a marimbists’ expressive bodily behaviors in an audio-visual performance recording. For one percussionist, this was a self-reflective analysis. The work was unfamiliar to the other percussionist and singer. Perception of the performer’s expressive bodily behaviors differed according to participants’ individual instrumental or vocal motor expertise, and familiarity with the music. Furthermore, individual type of motor experience appeared to direct participants’ attention in approaching the analyses. Findings support forward and inverse perception-action models, and embodied cognitive theory. Implications offer scientific rigour and artistic interest for how performance practitioners can reflectively analyze performance to improve expressive communication.